2004
DOI: 10.2337/diacare.27.6.1313
|View full text |Cite
|
Sign up to set email alerts
|

The Coping Styles of Adolescents With Type 1 Diabetes Are Associated With Degree of Metabolic Control

Abstract: OBJECTIVE -To systematically study the various coping styles in a population-based sample of adolescents with type 1 diabetes, exploring the association of different coping styles with metabolic control and adolescent self-reported diabetes-related quality of life.RESEARCH DESIGN AND METHODS -Of a total population of 116 adolescents with type 1 diabetes (age 13-18 years), 103 (89%) participated in the study, completing a questionnaire to obtain information on coping styles and perception of diabetes-specific q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
101
0
5

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 110 publications
(115 citation statements)
references
References 23 publications
9
101
0
5
Order By: Relevance
“…Another study with adolescents with type 1 DM by Graue et al reported that health-related quality of life perceptions were not affected by HbA1c but age and gender were influential. In the same study, it was found that adolescents with type 1 DM had worse quality of life perceptions compared to the healthy group (29).…”
Section: Discussionmentioning
confidence: 78%
“…Another study with adolescents with type 1 DM by Graue et al reported that health-related quality of life perceptions were not affected by HbA1c but age and gender were influential. In the same study, it was found that adolescents with type 1 DM had worse quality of life perceptions compared to the healthy group (29).…”
Section: Discussionmentioning
confidence: 78%
“…Findings from studies in diabetes indicate that greater use of avoidant (or emotion-focused) coping strategies such as wishful thinking in response to stress is related to poorer metabolic control 21,22 and poorer psychosocial outcomes, including lower reported quality of life, more depressive symptoms, and lower social competence. 22 In contrast, greater use of approach (or problem-focused) coping strategies has been related to better metabolic control and better psychosocial adjustment in youths with type 1 diabetes.…”
Section: Coping Skills Training For Youths With Diabetesmentioning
confidence: 99%
“…22 In contrast, greater use of approach (or problem-focused) coping strategies has been related to better metabolic control and better psychosocial adjustment in youths with type 1 diabetes. 23,24 Similarly, greater use of avoidant coping and less use of approach coping has been related to poorer adherence to treatment regimen.…”
Section: Coping Skills Training For Youths With Diabetesmentioning
confidence: 99%
“…Early diagnosis and treatment of psychiatric conditions coexisting and complicating DM management have been shown to improve treatment outcomes such as hemoglobin A1C levels (36). DM, when diagnosed early in life in young children and adolescents has profound effects on psychological development leading to lifelong patterns of faulty coping mechanisms including self-destructive behaviors, aggressiveness, anxieties about their disease state, and not being able to utilize healthy coping skills leading to disengagement and poor adherence (36).…”
Section: Management Of Psychiatric Comorbiditiesmentioning
confidence: 99%
“…DM, when diagnosed early in life in young children and adolescents has profound effects on psychological development leading to lifelong patterns of faulty coping mechanisms including self-destructive behaviors, aggressiveness, anxieties about their disease state, and not being able to utilize healthy coping skills leading to disengagement and poor adherence (36). The presence of these disengaging behaviors and defiant attitudes makes it difficult to have an in-depth evaluation leading to proper diagnosis.…”
Section: Management Of Psychiatric Comorbiditiesmentioning
confidence: 99%